The Screaming Body: Non-Realistic Actors' Resistance to the Aesthetics of Digital Imaging in Zarathustra's Staging - Qadar Basri, syaiful; Hariyanto , Moh.; Mujib Al Firdaus, Moh.; Suryandoko, Welly (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
This article examines the performance of Zarathustra by students of the UNESA Sendratasik Education Study Program as a form of resistance to the aesthetics of digital imagery through the practice of non-realistic role-playing art. This research aims to examine how actors' bodies are used as a medium of authentic expression and an arena of resistance to identity homogenization in the social media era. With a qualitative-descriptive approach and a case study design, data were obtained through participatory observation, visual documentation, and semi-structured interviews, and analyzed using a hermeneutic phenomenological approach. The results of the study show that the actor's body is positioned not just as a tool of dramatic representation, but as a performative entity that is alive, vulnerable, and existentially honest. The performance conceptually combines Friedrich Nietzsche's Übermensch theory and Jerzy Grotowski's principles of Poor Theater, which emphasizes the purification of expression and the spirituality of the body. These findings expand the discourse of contemporary performing arts by offering a model of creation that rejects the aesthetics of digital curation and emphasizes the presence of the authentic body. The implications of the research have an impact on the pedagogy of the role arts and performance creation strategies that are more reflective, critical, and contextual to contemporary cultural issues.